Old Habits Die Hard: Dietary Habits of Migraine Patients Challenge our Understanding of Dietary Triggers - Lisicki, Marco; Schoenen, Jean (Frontiers in Neurology, 2021)
Introduction Migraine is a multifactorial neurological disorder with a major metabolic facet. Dietary approaches represent a commonly implemented lifestyle modifying strategy in headache clinics, yet the precise relationship between diet and migraine is still a matter of debate. Materials and methods The study consisted of two parts: first, in a cross-sectional design, we compared alimentary habits of migraine subjects and a control group of healthy volunteers. For the second part, we prospectively evaluated patients’ daily consumption of various potentially migraine-triggering foods over a two-month period in order to examine their possible association with the occurrence of a migraine attack. Results Most migraine patients reported avoiding at least one potentially migraine-triggering food/drink from their diet. In spite of that, with the sole exemption of citrus fruits, there were no statistically significant differences with respect to consumption patterns between migraine patients and controls (including wine and chocolate). Consumption frequency over time was proportional to intake of potentially migraine-triggering foods the day before a migraine attack. Conclusion Our results underline the need of performing trigger challenges in order to avoid falling into an association-causation fallacy when attempting to identify possible alimentary migraine triggers. Indeed, it is possible that intake of certain foods like chocolate before attacks is a consequence of pre-attack cravings or a simple coincidence facilitated by previously established dietary habits.